Cyclodextrin as Functional Carrier in Development of Mucoadhesive Tablets Containing Polygoni cuspidati Extract with Potential for Dental Applications - Magdalena Paczkowska-Walendowska; Emilia Szymańska; Katarzyna Winnicka; Dominik Szwajgier; Ewa Baranowska-Wójcik; Marek A. Ruchała; Marek Simon; Judyta Cielecka-Piontek (MDPI AG, 2021)
Polygoni cuspidati root is a resveratrol-rich source with anti-inflammatory, angiogenic and neuroprotective effects. The raw material was standardized for the content of resveratrol, for which there is a special justification for administration within the oral mucosa. To improve the solubility of resveratrol and to assure its high content in plant material, an ultrasound-assisted extraction method was applied. The addition of cyclodextrin was found to increase the extraction efficiency of resveratrol (from 13 to 297 µg per 1 g of plant material in case of 50% ethanol extracts) and enhanced its antioxidant activity as compared to pure Polygoni cuspidati extract/resveratrol. Cyclodextrin plays the role of a functional extract regarding technological properties (increasing the extraction of resveratrol from the extract, improving mucoadhesive properties). Therefore, the aim of this study was to develop mucoadhesive tablets containing combinations of the Polygoni cuspidati extract with a cyclodextrin carrier for buccal delivery. The tests sequentially included extract preparation and characterization of its physical and biological properties and then formulation studies with a broad description of the prototype properties. The test results indicate that cyclodextrin increases the efficiency of resveratrol extraction from Polygoni cuspidati rhizome, which is a rich source of resveratrol, and its extract enclosed in a mucoadhesive tablet guarantees prolonged action at the site of administration.